Using Input from Realtors to Improve Housing Counseling Programs. (2nd September 2013) - Aaberg, Jordan J.; Delgadillo, Lucy M.
Abstract : Realtors can be described as valuable, nonevaluator stake holders. Realtors can be involved in either motivating the public to become educated about the home buying process or Realtors might be involved in discouraging clients from becoming informed. The framework that guided this research was program evaluation theory. The authors believed that surveying Realtors would provide useful information for improving first‐time home buyer (FTHB) workshops and for increasing the credibility of housing counseling agencies. The results of a survey indicated that Realtors perceived FTHB workshops to be "somewhat useful." However, a majority of the Realtors opposed mandatory FTHB workshops, perceiving them as one more barrier for sales. Responses to an open‐ended question showed that Realtors perceived the most troubling issue for FTHBs was experiencing underwriting delays when obtaining a mortgage. Providers of homeownership education can consider this information when evaluating their workshops to improve the effectiveness of FTHB education.